Refractive index and sensing of glucose molarities determined using Au-Cr K-SPR at 670/785 nm wavelength - P. Susthitha Menon,; Mulyanti, Budi; Nur Akmar Jamil,; Wulandari, Chandra; Nugroho, Harbi Setyo; Gan, Siew Mei; Noor Faizah Zainul Abidin,; Hasanah, Lilik; Pawinanto, Roer Eka; Dilla Duryha Berhanuddin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this paper, we determine the optical refractive indices of different molarities of glucose using nano-laminated gold/chromium (Au-Cr) thin film via Kretschmann-based Surface Plasmon Resonance (K-SPR) sensing with angular interrogation. The nano-laminated Au-Cr K-SPR sensor detects the glucose presence in low- and high-concentration of 4-12 mmol/L and 55-277 mmol/L, respectively, under the exposure of 670 nm and 785 nm optical wavelengths. The experimental results showed that the minimum limit of detection (LOD) of Au-Cr K-SPR is 4 mmol/L and the glucose sensor sensitivities are in average of 3.41 o/M and 2.73o/M at 670 nm and 785 nm optical wavelength, respectively. Stable sensitivity for each concentration also shown from the sensorgram results, indicates the stable performance of nano-laminated Au-Cr SPR sensor to detect glucose in the range from mmol/L up to dmol/L. Values of refractive indices for glucose molarities obtained are 1.33187 (4 mmol/L) and 1.3191 (4 mmol/L) at 670 and 785 nm wavelength, respectively. These RI values are beneficial for numerical simulation of glucose sensors using nano-laminated Au-Cr thin films which have been reported for the first time. The sensor can be eventually deployed in integrated photonic sensing devices comprising of multiple analyte detection for lab-on-chip (LoC) and point-of care (PoC) applications.